Іnstitute impeachment system constitutional and legal responsibility - Tsymbalistyi, Taras (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article deals with the concept and nature of impeachment. Analyzes the constitutional and legal provisions on impeachment, defined problems of its realization in Ukraine. Made suggestions for improving the current legislation in this area